Fluorescence in situ hybridization (FISH) mapping of single copy genes on Trichomonas vaginalis chromosomes - Zubáčová, Zuzana; Krylov, Vladimír; Tachezy, Jan (Molecular and biochemical parasitology, 2011)
The highly repetitive nature of the Trichomonas vaginalis genome and massive expansion of various gene families has caused difficulties in genome assembly and has hampered genome mapping. Here, we adapted fluorescence in situ hybridization (FISH) for T. vaginalis, which is sensitive enough to detect single copy genes on metaphase chromosomes. Sensitivity of conventional FISH, which did not allow single copy gene detection in T. vaginalis, was increased by means of tyramide signal amplification. Two selected single copy genes, coding for serine palmitoyltransferase and tryptophanase, were mapped to chromosome I and II, respectively, and thus could be used as chromosome markers. This established protocol provides an amenable tool for the physical mapping of the T. vaginalis genome and other essential applications, such as development of genetic markers for T. vaginalis genotyping.
Keywords: Gene Dosage; serin-C-palmitoyltransferasa; Tryptophanase; Chromosome Mapping; chromozomy; Trichomonas Infections; Genotype; hybridizace in situ fluorescenční; genová dávka; DNA fingerprinting; DNA Fingerprinting; Antigens, Protozoan; Trichomonas vaginalis; antigeny protozoální; Fluorescence; genetické markery; Serine C-Palmitoyltransferase; trichomoniáza; genom; lidé; ženské pohlaví; Chromosomes; mapování chromozomů; Humans; Sensitivity and Specificity; senzitivita a specificita; tryptofanasa; In Situ Hybridization, Fluorescence; genotyp; Genome; Female; Genetic Markers; fluorescence